2020
DOI: 10.3390/molecules25133002
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Anthelmintic Evaluation of Gliricidia sepium, Leucaena leucocephala, and Pithecellobium dulce: Fingerprint Analysis of Extracts by UHPLC-Orbitrap Mass Spectrometry

Abstract: In the present work, the anthelmintic activity (AA) of ethanolic extracts obtained from Gliricidia sepium, Leucaena leucocephala, and Pithecellobium dulce was evaluated using the third-stage-larval (L3) exsheathment inhibition test (LEIT) and egg hatch test (EHT) on Haemonchus contortus. Extracts were tested at concentrations of 0.3, 0.6, 1.2, 2.5, 5.0, 10, 20, and 40 mg/mL. The larval exsheathment inhibition (LEI) results showed that G. sepium achieved the highest average inhibition of 91.2%, compared with 44… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
11
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 82 publications
6
11
1
1
Order By: Relevance
“…The egg-laying activity in this study was also found to be significantly reduced after exposure to LL extract and mimosine, as demonstrated by the decrease in the mean number of eggs laid. Similar research findings concordantly showed the inhibition of egg-laying and -hatching post-treatment with LL extracts in different nematode species [ 30 , 32 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ]. For instance, a recent study by Romero et al (2020) [ 76 ] reported that the ethanolic extract of LL leaves significantly inhibited egg-hatching activity up to 54% in Haemonchus contortus.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The egg-laying activity in this study was also found to be significantly reduced after exposure to LL extract and mimosine, as demonstrated by the decrease in the mean number of eggs laid. Similar research findings concordantly showed the inhibition of egg-laying and -hatching post-treatment with LL extracts in different nematode species [ 30 , 32 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ]. For instance, a recent study by Romero et al (2020) [ 76 ] reported that the ethanolic extract of LL leaves significantly inhibited egg-hatching activity up to 54% in Haemonchus contortus.…”
Section: Discussionsupporting
confidence: 82%
“…Similar research findings concordantly showed the inhibition of egg-laying and -hatching post-treatment with LL extracts in different nematode species [30,32,[74][75][76][77][78][79][80]. For instance, a recent study by Romero et al (2020) [76] reported that the ethanolic extract of LL leaves significantly inhibited egg-hatching activity up to 54% in Haemonchus contortus. These studies strongly support the ability of LL plant extracts to inhibit the laying and hatching of eggs in nematodes.…”
Section: Discussionsupporting
confidence: 69%
“…The last herb component, P. dulce , contained many chemical groups with antioxidant effects that were similar to those of the two previous herbs, such as glycosylated compounds and flavonoids (quercetin-3-glucoside, luteolin-7-O-glucoside, and kaempferol-3-O-rhamnoside) as well as fatty acids (azelaic acid, etc.) [ 45 ]. The chemicals found in the herbal components and Tri-TT remedy belonged to similar chemical groups as the primary and secondary metabolite constituents of plant parts, with an emphasis on phenolic compounds and flavonoids with potent antioxidant activities ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Still, the considerably lower amount of flavonoid glycosides in the inflorescences extract perhaps may have unmasked the interactions with other metabolites present (e.g., proanthocyanidins and luteolin) leading to improved anthelmintic effects. Flavonoid glycosides have been identified in the chemical profile of several plant species with proven anthelmintic effects ( Barrau et al, 2005 ; Mengistu et al, 2017 ; Araújo et al, 2019 ; Romero et al, 2020 ), and some authors have posed the possibility of occurring interactions of this type of compounds with GIN ( Barrau et al, 2005 ; Alonso-Díaz et al, 2008 ). Barrau et al (2005) determined that 3 flavonol glycosides (quercetin-3- O -rutinoside or rutin, kaempferol-3-rutinoside or nicotiflorin and isorhamnetin-3-rutinoside or narcissin) reduced the migration of H. contortus L3 larvae in 25–35% when applied at 1,200 μg mL –1 .…”
Section: Discussionmentioning
confidence: 99%